2009
DOI: 10.1073/pnas.0909751106
|View full text |Cite
|
Sign up to set email alerts
|

Gray and white matter changes associated with tool-use learning in macaque monkeys

Abstract: We used noninvasive MRI and voxel-based morphometry (VBM) to detect changes in brain structure in three adult Japanese macaques trained to use a rake to retrieve food rewards. Monkeys, who were naive to any previous tool use, were scanned repeatedly in a 4-T scanner over 6 weeks, comprising 2 weeks of habituation followed by 2 weeks of intensive daily training and a 2-week posttraining period. VBM analysis revealed significant increases in gray matter with rake performance across the three monkeys. The effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
150
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(163 citation statements)
references
References 50 publications
(54 reference statements)
11
150
2
Order By: Relevance
“…These results may also be considered as providing a structural basis for previously observed functional brain changes (shown by functional MRI) during category learning (of dot patterns) (32). The time course of cortical changes in gray matter in the human adult brain remains to be established (33), and the question of how cortical changes at the macroscopic and the synaptic levels are related to each other is still to be answered. Although there is still much to be learned on all of these issues, the present study strengthens the proposition that the intact human adult brain is structurally more plastic than previously believed.…”
Section: Resultsmentioning
confidence: 66%
“…These results may also be considered as providing a structural basis for previously observed functional brain changes (shown by functional MRI) during category learning (of dot patterns) (32). The time course of cortical changes in gray matter in the human adult brain remains to be established (33), and the question of how cortical changes at the macroscopic and the synaptic levels are related to each other is still to be answered. Although there is still much to be learned on all of these issues, the present study strengthens the proposition that the intact human adult brain is structurally more plastic than previously believed.…”
Section: Resultsmentioning
confidence: 66%
“…In fact, not only can macaques be trained to use a variety of tools, but their use can be partially generalized to other objects and contexts. Interestingly, Iriki and co-workers [33,51] showed direct evidences of tool use-induced anatomical modifications in the temporal and parietal cortices, and the development of new cortico-cortical connections. Furthermore, this plasticity process appears to involve regions that are crucial for hand grasping [52].…”
Section: Conclusion and Evolutionary Remarksmentioning
confidence: 99%
“…Voxel-wise statistical tests are then performed on these tissue maps to identify group-wise differences or longitudinal changes based on the General Linear Model (GLM) (Ashburner & Friston 2000). For example, a longitudinal paradigm has revealed that training induces grey/white matter volume changes in macaques (Quallo et al 2009). VBM can also highlight phenotypic variations.…”
Section: Morphometry -Quantitative Studiesmentioning
confidence: 99%